Menegerial Assistance and Organizational Strengthening in Melati Jaya Cooperative: Pendampingan Menegerial Dan Penguatan Keorganisasian Pada Koperasi Melati Jaya - Tety Rachmawati; Rahayu Lestari; Fisko Arya Kamandanu; Dani Sayhrobi (Program Studi Hubungan Internasional FISIP UNILA, 2023)
Poverty alleviation solutions can be achieved by increasing the economic resilience of the community. Koperasi Melati Jaya, Sukamenanti Village, was established as an effort to strengthen the economic resilience of the community. However, its operations experience obstacles and obstacles such as the absence of internetbased correspondence and lack of knowledge about cooperative partnership programs. This service aims to provide managerial assistance to members of the Melati Jaya Cooperative in digitizing correspondence and explaining the cooperative partnership system. This service activity was carried out by conducting training on digitizing correspondence and socializing partnerships. The results obtained from this service show that most members of the Melati Jaya Cooperative can digitize correspondence and understand cooperative partnership proposals